학생반응으로 살펴본 문제바탕학습 교육과정의 질적 평가 - 김주희(Ju-Hui Kim); 김지영(Ji Young Kim); 손희정(Hee Jung Son); 최윤호(Yoon-Ho Choi); 홍경표(Kyung-Pyo Hong); 안병헌(Byung (Korean journal of medical education, 2004)
Purpose: Recently established in 1997, Sungkyunkwan University School of Medicine was the first medical school in Korea to adopt problem-based learning (PBL) as a core curriculum from the very beginning. The purpose of this study was to evaluate the PBL curriculum from the viewpoint of the medical students. Methods: This study used a qualitative approach to understand students' perceptions of the positive aspects of PBL. A total of 22 second-year medical students at Sungkyunkwan medical school were surveyed. Student perceptions were obtained from questionnaires and face-to-face interviews. The interview was designed to evoke more personal and in-depth responses. Results: Students' perceptions of the effects of PBL were found to be very favorable. Most students showed positive responses on issues of more active learning attitude, self-directed learning, motivation to study, improved problem solving, and integrated learning. Conclusion: The results of this study demonstrated that the students had a good understanding of PBL and experienced its positive aspects. It might be concluded that PBL was successfully implemented into the curriculum and the specific and expected effects of PBL accomplished. KCI Citation Count: 11